(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article analyzes the results of the studies on the formation and development of visual perception of visually impaired children in the aspect of correction and prevention of optical-graphic writing disorders, conducted by foreign and domestic authors. First of all, the importance of the problem is determined by the fact that the visual impairment makes the process of reading and writing of these children much more difficult. Owing to the insufficient development of visual perception, visually impaired students write letters, syllables or words together or excessively apart, dislocate the writing straightness etc. Therefore, the correction and prevention of this kind and other optical-graphic writing dislocations of visually impaired students has utmost importance. Тhe special scientific and methodological literature pays great attention to the issues connected with the formation and development of visual perception of children with visual impairment in, many foreign and domestic researchers do research in this field. However, conducted works lack due attention to the development of visual perception of visually impaired children within the scope of correction and prevention of optical-graphic writing disorders. Whereas the solution to this problem is very important for these children. Therefore, the question to explore the ways and means of creation and development of techniques of visual perception, reading of flat surfaces, the correction of optic-graphic writing skills of children with visual impairment has an important significance for the theory and practice of teaching the students in special, inclusive and mainstream schools. The above stated determines the relevance of this study, its theoretical and practical significance.